Deskripsi Kerusakan Ekosistem Hutan Mangrove - Sitti Saidah; La Harudu; Sitti Kasmiati; Surdin (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2024)
The mangrove forest habitat in Tangofa Village is indicated to have been degraded due to land conversion and pollution. This research aims to determine the level of damage to the mangrove forest ecosystem based on vegetation cover and vegetation density and to determine the factors that influence damage to the mangrove forest ecosystem in Tangofa Village. Data collection was carried out using survey methods and direct interviews. Based on the results of the analysis of relative cover and species density obtained from the results of the analysis, it ranges from 23%-43%, where based on the 2004 ministerial decision, the level of damage to the mangrove ecosystem for each mangrove species is <50% in the rare/damaged category. The total density at the seedling-tree level is 350-600 trees/ha, the standard criteria for the level of damage to the mangrove forest ecosystem is a tree density of <1000 trees/ha with rare/damaged conditions. Factors causing damage to the mangrove forest ecosystem in Tangofa Village are a lack of knowledge about mangroves, nickel mining activities, waste disposal, development of residential land, and felling of mangrove trees.